EFEKTIVITAS PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR IPA - SUNARSIH SUNARSIH (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
This research is Classroom Action Research (CAR) using the Discovery Learning learning model. The problem formulated in this study is how effective the application of the discovery learning method is on science learning outcomes for students in class VII E MTsN 5 Jombang. The research was conducted on class VII E MTsN 5 Jombang students for the 2022/2023 school year with a total of 32 students. The instrument used in this research is the learning achievement test. The learning outcomes test is a class action research ability test in the form of a written test that focuses more on Environmental Pollution material. The data collection technique used in this study was a written test. The tests carried out at the beginning of the study, namely pre-cycle, cycle I and cycle II were analyzed using evaluation results analysis techniques to determine learning completeness both individually and classically by analyzing written test results data using learning completeness criteria. The percentage of learning outcomes obtained by these students is then compared with the KKM that has been determined by the school/madrasah. A student is said to have completed learning if he has achieved a score of ? 75. This is based on the KKM from MTsN 5 Jombang and classical completeness if 85% of the class achieves a score of 75 and above. To calculate student learning outcomes, the percentages correction formula is used. ABSTRAKPenelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan menggunakan model pembelajaran Discovery Learning. Masalah yang dirumuskan dalam penelitian ini adalah bagaimana efektivitas penerapan metode discovery learning terhadap hasil belajar IPA pada peserta didik kelas VII E MTsN 5 Jombang. Penelitian dilaksanakan pada peserta didik kelas VII E MTsN 5 Jombang tahun ajaran 2022/2023 dengan jumlah peserta didik sebanyak 32 anak. Instrumen yang digunakan pada penelitian ini adalah tes hasil belajar. Tes hasil belajar sebagai tes kemampuan penelitian tindakan kelas berupa tes tertulis yang lebih menitik beratkan pada materi Pencemaran Lingkungan. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah tes tertulis. Tes dilaksanakan pada awal penelitian yaitu prasiklus, siklus I dan siklus II dianalisis dengan teknik análisis hasil evaluasi untuk mengetahui ketuntasan belajar baik secara individual maupun secara klasikal dengan cara menganalisis data hasil tes tertulis menggunakan kriteria ketuntasan belajar. Persentase hasil belajar yang diperoleh peserta didik tersebut kemudian dibandingkan dengan KKM yang sudah ditentukan oleh Sekolah/Madrasah. Seorang peserta didik disebut tuntas belajar jika telah mencapai skor ? 75. Hal ini berdasarkan pada KKM dari MTsN 5 Jombang dan ketuntasan klasikal apabila 85% kelas mencapai skor 75 ke atas. Untuk menghitung hasil belajar siswa digunakan rumus percentages correction.